Boosting Productivity for Advanced Biomanufacturing by Re-Using Viable Cells - Reger, Lucas Nik; Saballus, Martin; Matuszczyk, Jens; Kampmann, Markus; Wijffels, Rene H.; Martens, Dirk E.; Niemann, Julia (Frontiers in Bioengineering and Biotechnology, 2023)
Monoclonal antibodies (mAb) have gained enormous therapeutic application during the last decade as a highly efficient and flexible tools for the treatment of various diseases. Despite this success there remain opportunities to drive down the manufacturing costs of antibody-based therapies by cost efficiency opportunities. To reduce production costs, novel process intensification, based on state of the art fed-batch and perfusion, have been implemented during the last few years. Building on process intensification, we demonstrate the feasibility and benefits of a novel innovative hybrid process that combines the robustness of a fed-batch operation with the benefits of a complete media exchange enabled through a fluidized bed centrifuge (FBC). In an initial small-scale FBC-mimic screening we investigated multiple process parameters, resulting in increased cell proliferation and elongated viability profile. Consecutive, the most productive process scenario was transferred to 5 L scale, further optimized and compared to a standard fed-batch process. Our data show that the novel hybrid-process enables significantly higher peak cell densities (163 %) and an impressive increase in mAb amount of approximately 254 %, while utilizing the same reactor size and process duration of the standard fed-batch operation. Further, our data show comparable CQA between the processes and reveal scale-up possibilites and no need for extensive additional process monitoring. Therefore, this novel process intensification strategy yields strong potential for transfer into future industrial manufacturing processes.